2010
DOI: 10.1097/ta.0b013e3181b28b8c
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneocuboid Joint Involvement in Calcaneal Fractures

Abstract: These results indicate that calcaneal fractures with involvement of the CCJ are associated with more severe trauma and worse outcome. Thus, the CCJ should be given more credit during surgery and in our research efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
0
26
1
1
Order By: Relevance
“…Patient-related items were: gender, age at trauma, trauma mechanism and Injury Severity Score (ISS). Fracture characteristics were: presence of varus tilt of the talus [1], double density sign [4,6], the involvement of the calcaneocuboid joint (CCJ) [7,8], associated fibula fracture [2] and Essex-Lopresti and Sanders classification (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Patient-related items were: gender, age at trauma, trauma mechanism and Injury Severity Score (ISS). Fracture characteristics were: presence of varus tilt of the talus [1], double density sign [4,6], the involvement of the calcaneocuboid joint (CCJ) [7,8], associated fibula fracture [2] and Essex-Lopresti and Sanders classification (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Soft tissue coverage was achieved in 8 patients using a free vascular flap, in 5 patients using a pedicled flap, 17 times using split skin grafts, and 4 times using full skin grafts. On average, four operations were necessary (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] to achieve soft tissue coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable with prior studies, we could show that alterations in gait were found even with minor changes of anatomy. 15,22 Only 22% of the patients had symmetric cyclograms. As with all methods, pedography has its limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations